An improved weather routing method based on non-uniform waypoint network - Cao, Ran; Qian, Longxia; Hong, Mei; Li, Dongyu; Zhu, Tianhao (Ocean engineering, 2025)
Maritime navigation safety is critical in case of frequent accidents caused by adverse weather. This paper proposes a novel ship weather routing (SWR) method to develop safer ocean navigation routes. First, a non-uniform waypoint network is generated through an improved Sparrow Search Algorithm (SSA). Subsequently, a Non-Uniform A∗ (NUA∗) algorithm is proposed by using the non-uniform waypoint network as the search space. The algorithm considers navigational risks and time factors, while incorporating constraints based on the International Maritime Organization (IMO) regulations. The non-uniform waypoint network features a higher density of nodes in higher-risk navigable areas, thereby providing enhanced routing options, and enabling the NUA∗ to generate safer routes. Moreover, sensitivity experiments are performed on key parameters to improve algorithm performance. Finally, NUA∗ is applied to a maritime accident case. The results show that NUA∗ effectively guides the ship to avoid risks. Compared with uniform networks, the non-uniform network shows 8.48 %–12.61 % fewer IMO violations with higher node utilization. The risk of NUA∗ route is reduced by 2.46 %–15.66 % compared to A∗ and BA∗, and the wave height in the areas traversed by NUA∗ route is decreased by 2.87 %–20.29 %. Therefore, NUA∗ can provide superior and safer route solutions. •A non-uniform waypoint network is generated by an improved Sparrow Search Algorithm.•A Non-Uniform A∗ algorithm is proposed to develop safer ocean navigation routes.•The Non-Uniform A∗ can provide superior route solutions for ocean navigation.